Faek Rasul: Memories of Political Violence Transformed in the Materials of Painting (Zeitschrift für Migrationsforschung, 2024)
This article focuses on the artistic work of the Kurdish-Austrian, Iraqi-born painter Faek Rasul within a biographical context. Belonging to a clandestine Kurdish political organization, Rasul was imprisoned in 1980, tortured, and lost many friends and fellow prisoners to execution. He escaped from Iraq to Iran and finally came to Austria in 1987, where he artistically elaborated his memory of the atrocities he and his companions suffered in a process of constant transformation over four decades. Based on extended interviews, the article follows Rasul’s biography and trajectory of memory after fleeing and settling in Austria. The course of memory is differentiated along intertwining aspects of involuntary, intrusive memory and deliberate, active memory. Active memory is explored in different settings. They comprise the artistic work process, in which arts and crafts materials are imbued with specific meanings, as well as former sites of sufferance in Iraq, where Rasul recollected traces of victims that again became part of his art.Faek Rasul: Erinnerungen an politische Gewalt, transformiert in den Materialien der MalereiDer Artikel untersucht das künstlerische Werk des kurdisch-österreichischen, im Irak geborenen Künstlers Faek Rasul im biografischen Kontext. Rasul wurde 1980 als Mitglied einer klandestinen kurdischen Organisation verhaftet, gefoltert und erlebte die Misshandlung und Exekution zahlreicher Freunde und Mithäftlinge. Nach seiner Freilassung floh er in den Iran und gelangte schließlich 1987 nach Österreich, wo er seine Erinnerungen an die Gräuel, die er erlitt und bezeugte, in einem Prozess konstanter Transformation über vier Jahrzehnte künstlerisch bearbeitete. Auf Grundlage mehrstündiger Interviews folgt der Artikel Rasuls Biografie und dem Erinnerungsprozess nach seiner Flucht und nachdem er sich in Österreich niederließ. Die Gedächtnisvorgänge werden nach Aspekten der unwillkürlichen, traumatischen Erinnerung (intrusive memory) und nach bewussten, aktiven Erinnerungsakten analysiert. Aktive Erinnerung wird in unterschiedlichen Settings untersucht: im künstlerischen Arbeitsprozess, in dem die Materialien der Malerei mit spezifischen Bedeutungen verknüpft werden; und im Zuge der Rückkehr zu Orten des Grauens im Irak, wo Rasul Spuren von Opfern dokumentierte, die er wiederum künstlerisch verarbeitete.
Keywords: Migration; Kunst; transkulturelle Erinnerung; traumatische Erinnerung; politische Gräuel; irakische Kurden